IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI TERHADAP PEMBUBARAN PARTAI POLITIK DI INDONESIA - Hasir Budiman Ritonga (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
Judicial power in Indonesia under the 1945 Constitution of the Republic of Indonesia shall be exercised by the Supreme Court and the Constitutional Court. One of the authority of the Constitutional Court according to the 1945 Constitution of the Republic of Indonesia is to decide the dissolution of political parties. The facts in the current Indonesian system of ketatanegaran no cases of political parties that were dissolved through the decision of the Constitutional Court, it's just that the problem is when the Constitutional Court uses its authority to break the dissolution of political parties there are things that are formal juridically there is no clear rules, such as the legal status of party members who are not directly involved in the violation committed by the party and the status of party members who hold the position of members of the legislature both at the center and in the regions. So for that must be resolved by emphasizing the certainty, justice and benefit in the decision of the constitutional court.